2020
DOI: 10.1097/fjc.0000000000000892
|View full text |Cite
|
Sign up to set email alerts
|

Investigational Anti–Atrial Fibrillation Pharmacology and Mechanisms by Which Antiarrhythmics Terminate the Arrhythmia: Where Are We in 2020?

Abstract: : Antiarrhythmic drugs remain the mainstay therapy for patients with atrial fibrillation (AF). A major disadvantage of the currently available anti-AF agents is the risk of induction of ventricular proarrhythmias. Aiming to reduce this risk, several atrial-specific or -selective ion channel block approaches have been introduced for AF suppression, but only the atrial-selective inhibition of the sodium channel has been demonstrated to be valid in both experimental and clinical studies. Among the othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 151 publications
(373 reference statements)
0
11
0
1
Order By: Relevance
“…Atrial-selective inhibition of I Na is shown by us and others to be valid in terms of anti-AF efficacy and safety in both experimental and clinical studies [169174]. Atrial-selective prolongation of ERP and anti-AF efficacy of I Kur and SK channel blockers have turned out to be largely or exclusively owing to concomitant atrial-selective inhibition of I Na [171,175]. Ranolazine effectively terminate AF owing to an atrial-selective sodium channel blocking effect combined with I kr blocking in various AF models [169,176178].…”
Section: Drug and Ablation Development Of Atrial Fibrillationmentioning
confidence: 99%
See 1 more Smart Citation
“…Atrial-selective inhibition of I Na is shown by us and others to be valid in terms of anti-AF efficacy and safety in both experimental and clinical studies [169174]. Atrial-selective prolongation of ERP and anti-AF efficacy of I Kur and SK channel blockers have turned out to be largely or exclusively owing to concomitant atrial-selective inhibition of I Na [171,175]. Ranolazine effectively terminate AF owing to an atrial-selective sodium channel blocking effect combined with I kr blocking in various AF models [169,176178].…”
Section: Drug and Ablation Development Of Atrial Fibrillationmentioning
confidence: 99%
“…Although new drugs blocking I KACh have not emerged for clinical use, inhibition of I KACh remains a promising therapeutic target for the management of AF. Atrial-selective inhibition of I Na is shown by us and others to be valid in terms of anti-AF efficacy and safety in both experimental and clinical studies[169][170][171][172][173][174]. Atrial-selective prolongation of ERP and anti-AF efficacy of I Kur and SK channel blockers have turned out to be largely or exclusively owing to concomitant atrial-selective inhibition of I Na[171,175].…”
mentioning
confidence: 95%
“…Аритмії часто зустрічаються як у хворих із серцево-судинними захворюваннями, так і серед здорових осіб, нерідко спричиняючи смерть та інвалідизацію [1][2][3][4]. Останніми роками для лікування суправентрикулярних аритмій, особливо фібриляції передсердь (ФП), значного поширення набула транскатетерна абляція, однак важливу роль у лікуванні пацієнтів, як і раніше, відіграють антиаритмічні препарати (ААП) [1,5,6]. ААПгрупа лікарських засобів, що мають здатність впливати на систему електропровідності серця й підтримувати синусовий ритм.…”
Section: ключові слова: аритмія; лікування; флекаїніду ацетат; фібриляція передсердь; флекаїнідunclassified
“…Increased focal atrial triggered activity, mainly due to delayed afterdepolarizations (DADs) and micro-reentrant circuits are the main electrophysiological mechanisms in all types of AF (paroxysmal, persistent, and permanent) [ 6 ].…”
Section: Atrial Fibrillation Pathogenesismentioning
confidence: 99%